Analisis Manajemen Risiko Keselamatan & Kesehatan Kerja (K3) Menggunakan Metode HIRADC Pada Pekerjaan Konstruksi Gedung di PT.XYZ - M. Zaenal Anshori; Tranggono Tranggono (Jurnal Kendali Teknik dan Sains, 2024)
This journal discusses the application of the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method in the context of Occupational Safety and Health (K3). This research aims to identify potential hazards in the work environment, evaluate related risks, and determine effective control measures. The HIRADC method is used as a framework for developing holistic and evidence-based K3 action plans. The research results show that the application of the HIRADC method can increase understanding of risks in the workplace and provide a strong basis for proactive K3 management. This study contributes to the development of K3 strategies that are more efficient and oriented towards preventing work accidents in building construction work.